Evaluation of the Efficacy and Safety of Atropine Eye Drops 0.01% in Slowing Myopia Progression in Children and Adolescents with High and Low Myopia: A Quasi experimental study - Masud, Hannan; Batool, Fizzah; Nasir, Samra; Hannan, Sarah (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the efficacy and safety of Atropine eye drops 0.01% in slowing myopia progression in children and adolescents with high and low myopia.Study Design: Quasi experimental study.Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Sep 2021 to Jul 2024Methodology: Seventy-two patients (144 eyes) aged 5-18 years (8.47±3.04 years) with myopia progression (≥0.25mm AL or ≥0.75D SE over 3 months). Participants were stratified by high myopia (HM, AL>26.5mm, SE> -6D) and low myopia (LM, AL